Analisis Kualitas Produk dan Layanan Purnajual Terhadap Proses Keputusan Pembelian Konsumen Honda All New Vario 125 Melalui Citra Merek Sebagai Mediator - Edi Fitriana Afriza (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2019)
Research shown to identify and analyses the associated simultaneous or partially influence of product quality and after-sales service towards the brand image, as well as its implications on product purchase decision process is All New Honda Vario 125. Survey with quantitative descriptive analysis accompanied approach is used as a method of research supported through fieldwork, research instruments questionnaires, depth-interviews, and study of the literature to obtain primary and secondary data. Simple random sampling is a sampling technique that used the techniques of the obtained sample size as much as 119 respondents continued through path analysis, t-test, F-test, and sobel test to determine the results of the research. The results of the analysis it is known that the quality of products and services Post-sale partially and simultaneous effect significant towards product brand image Honda All New Vario 125. In addition, product quality and after-sales service are partial and simultaneous have influence on product purchase decision process is All New Honda Vario 125. It is Continued by testing the sobel test of brand image which had a significant influence of decision product purchase All New Honda Vario 125. It is conducted by indirect testing from both the product quality and after-sales service to purchase decision process through the brand image.